Reply to Bayrak’s comments on “An investigation of seismicity for western anatolia” by Sayil and Osmanşahin (2008) - Sayil, Nilgun; Osmansahin, Ilhan (Natural hazards (Dordrecht), 2009)
The author looked over the comments of Critle, and can say that this is not a scientific criticization. It is very clear that the subject of the paper is one of the general seismicity studies based on statistical methods for a defined region. Besides, it has similar format with such a kind of studies in literature (Papazachos 1989; Papazachos and Papaioannou 1993; Sayil and Osmansahin 2004; Sayil and Osmansahin 2005a, b; Sayil and Osmansahin 2006; Sayil 2007.